Towards a complex system of personal and group characteristics for ICT appropriation - Montes Agudelo, Daniel; Ramirez Castañeda, Luz Arabany; Sepúlveda López, Jheimer Julián (Journal of Sociocybernetics, 2018)
This research tackles the phenomenon of digital inclusion, considered as a type of social development that has grown, due to the advance of information and communication technologies (ICT). It is worth noting that, the "ICT advance" has not been uniformly distributed, since there is a difference regarding the access to technology, and to the use of it among groups and people. Though the governments, the organizations and the ICT institutions, recognize the social nature of the digital inclusion, and also, they are aware of the necessity of integrating communities and people, with the process of program and/or project management; these people and communities are not considered, in the proposals that are being made about this issue. Likewise, though it is clear in the revision of literature, the necessity of having quantitative and qualitative approaches, the numerical approach that is being performed in the phenomenon is evident. Additionally, it has been identified the fact that, there are diverse personal and social characteristics, that allow the appropriation of ICT tools, as well as their use to achieve goals and to improve the conditions, for participating in the employment, education and political activities. The digital inclusion is a situation that involves different factors, such as: cultural, technical, social, financial, regulatory, moral and even ecological. If this topic is tackled in a quantitative way, the aforementioned factors seem to be unrelated. However, in the literature analysis, their relation is obvious, as well as the fact that they cannot be unrelated form one another. In other words, the elements that conform the digital inclusion phenomenon, are not only heterogeneous, but also inter-definable. The former statement justifies the analysis of the digital inclusion phenomenon, as a complex system; since regarding the ICT appropriation, there is a wide variety of proposals, considering the personal and social variables, that regulate this process. Nevertheless, there is not yet a consensus about these variables, which is the proposal presented in this paper.